Kush - A Potential Biosorbent in the removal of Cd (II) and Zn (II) from aqueous solution - Kour, Jagjit; Homagai, P. L.; Pokherel, M. R.; Ghimire, K. N. (Journal of Nepal Chemical Society, 2012)
The industrial discharge of heavy metals into waters' course is one of the major pollution problems affecting water quality. Therefore, they must be removed prior to their discharge into waste streams. An efficient and low-cost bioadsorbent has been investigated from Desmostachya bipinnata (Kush) by charring with concentrated sulphuric acid and functionalized with dimethylamine.It was characterised by SEM, FTIR and elemental analysis. The effect of pH, initial concentration and contact time of the metal solution was monitered by batch method. The maximum adsorption capacities were determined for Cd and Zn at their optimum pH 6. The equilibrium data were analysed using Langmuir and Freundlich isotherm models. Langmuir isotherm model fitted well and the rate of adsorption followed the pseudo second order kinetic equation. DOI: http://dx.doi.org/10.3126/jncs.v27i1.6669 J. Nepal Chem. Soc., Vol. 27, 2011 107-114